Compliance of patients with chronic obstructive pulmonary disease to a pulmonary rehabilitation program - Janaina Schafer; Mariza Montanha Machado; Mirian Beatriz Reckiegel; Tania Cristina Malezan Fleig; Andreia Rosane Moura; Isabel Pommerehn Vitiello; Andréia Luica Gonçalves Silva (Universidade de Santa Cruz do Sul, 2012)
Background and Objectives: The lack of adherent and non-adherent to recommended treatment is a very common problem that interferes with the successful care and assistance to people with Chronic Obstructive Pulmonary Disease-COPD. This study compared the profi le of COPD patients that were adherent with non-adherent to a pulmonary rehabilitation program. Methods: was done an exploratory prospective observational study involving 24 patients with COPD Pulmonary Rehabilitation Program, divided into two groups according to full participation of the proposed treatment: Adhesive Group (GA = 18 subjects) and non-adherent (GN = 06 subjects). The treatment occurred in 08 weeks, 3 times a week, lasting 1 hour and 30 minutes, assisted by a multidisciplinary team composed by physiotherapist, physical education professional, nutritionist, pharmacist, psychologist and pneumologist. Results: The GA did not differ from GN about the situation sociodemographic, anthropometric, cardiopulmonary exercise capacity and respiratory function. GN had more comorbidities when compared to GA and higher average amount of drugs used. All patients were characterized with reduced quality of life and correlation between cardiac function and quality of life was seen for both groups. Conclusion: Our results show that the advanced stage of disease and worsening of symptoms were determinants for the adherence of patients with COPD in the Pulmonary Rehabilitation Program. KEYWORDS: COPD. Pulmonary Rehabilition. Interdisciplinary Health Team.